Evaluation of hyperspectral imaging as a modern aid in clinical assessment of burn wounds of the upper extremity. Issue 3 (May 2022) - Promny, Dominik; Aich, Juliane; Püski, Tamas; Marti Edo, Alejandro; Reichert, Bert; Billner, Moritz
Highlights: Hyperspectral Imaging parameter (StO2, THI, NIR) provide detailed insights into the perfusion of burn wounds. HSI is capable to distinguish burned skin from healthy skin. HSI shows possibility to even differentiate intermediate burns in certain parameters. Further research is necessary to set up data base for StO2, THI, and NIR reference values. Abstract: The most common burn wound assessment continues to be the clinical inspection and the tactile examination, which are subjective and remain challenging even for experienced burn surgeons. Recently, hyperspectral imaging camera systems have been increasingly used to support the evaluation of burn wounds. The aim of our study was to determine if hyperspectral imaging analysis differentiates and objectifies the assessment of burn wounds in burns of the upper extremities. We included 97 superficial partial, deep partial dermal burns, and full thickness burns. Hyperspectral imaging analysis was performed for all burns using proprietary software. The software recorded parameters for tissue oxygenation (StO2), tissue hemoglobin index, and near-infrared perfusion. These values were compared with the recordings for healthy, non-burned skin. We found that hyperspectral imaging analysis effectively differentiates burn wounds and shows the ability to distinguish even superficial partial burns from deep partial burns in the near-infrared perfusion analysis feature. Although, it was not possible to differentiate burn wounds in all features. Currently, it is important to optimize the respective reference values of the individual burn degrees for an objectified assessment.